Characterization of Sn–Sb–Ti Solder Alloy and the Study of Its Use for the Ultrasonic Soldering Process of SiC Ceramics with a Cu–SiC Metal–Ceramic Composite - Roman Kolenak (MDPI AG, 2021)
The aim of this research was to characterize soldering alloys of the type Sn–Sb–Ti and to study the ultrasonic soldering of SiC ceramics with a metal–ceramic composite of the type Cu–SiC. The Sn5Sb3Ti solder exerts a thermal transformation of a peritectic character with an approximate melting point of 234 °C and a narrow melting interval. The solder microstructure consists of a tin matrix, where the acicular constituents of the Ti6(Sb,Sn)5 phase and the sharp-edged constituents of the TiSbSn phase are precipitated. The tensile strength of the soldering alloy depends on the Ti content and reaches values from 34 to 51 MPa. The average strength of the solder increases with increasing Ti content. The bond with SiC ceramics is formed owing to the interaction of titanium, activated by ultrasound, with SiC ceramics, forming the (Ti,Si)6(Sb,Sn)5 reaction product. The bond with the metal–ceramic composite Cu–SiC is formed owing to the solubility of Cu in a tin solder forming two phases: the wettable η-Cu6Sn5 phase, formed in contact with the solder, and the non-wettable ε-Cu3Sn phase, formed in contact with the copper composite. The average shear strength of the combined joint of SiC/Cu–SiC fabricated using the Sn5Sb3Ti solder was 42.5 MPa. The Sn–Sb–Ti solder is a direct competitor of the S-Bond active solder. The production of solders is cheaper, and the presence of antimony increases their strength. In addition, the application temperature range is wider.